Analysis of the Dominant Internal and External Factors in the Performance of Human Resources in the Precast Company - Rachmawati, Dyah; Wijatmiko, Indradi; Devia, Yatnanta Padma (ASTONJADRO, 2023)
The performance of human resources (HR) in a company is one of the determinants of the company's condition in the industry. This can be analyzed based on the dominant factors that support or become the foundation of the company. This study reviews the dominant internal and external factors in PT.BEP company. The research method used is descriptive qualitative with analysis using IPA, Pareto Chart, IFAS-EFAS Matrix, and SWOT. The results showed that internal factors were dominated by ability factors with a processing value of 13.49%, while external factors were dominated by reward factors with a percentage of 16.42%. The results of the SWOT analysis recommend that the strategy that should be implemented is Strength-Opportunity (SO) with IFAS EFAS results in quadrant I with coordinates 1.67;2.34. then PT. BEP is in an advantageous situation because it has good strengths and opportunities and can be optimized by minimizing all weaknesses and threats.